Pingo Growth and collapse, Tuktoyaktuk Peninsula Area, Western Arctic Coast, Canada: a long-term field study - Mackay, J. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractGrowth data from precise surveys have been obtained for 11 pingos for periods ranging from 20 to 26 years. Most of the 1350 pingos, perhaps one quarter of the world's total, have grown up in the bottoms of drained lakes underlain by sands. Permafrost aggradation on the drained lake bottoms has resulted in pore water expulsion, solute rejection below the freezing front, a freezing point depression, and groundwater flow at below 0° C to one or more residual ponds, the sites of pingo growth. Sub-pingo water lenses underlie many growing pingos.The pure ice which grows by downward freezing in a sub-pingo water lens may be composed of seasonal growth bands which, like tree rings, are of potential use in the study of past climates. Growing pingos underlain by sub-pingo water lenses can often be identified by features such as peripheral pingo rupture, spring flow, frost mound growth, normal faulting, and oscillations in pingo height. Such features, and others, are associated with hydrofracturing and water loss from a sub-pingo water lens. Some of the data derived from the long-term study of pingo growth are relevant to the identification of collapse features, interpreted as paleo pingos, in areas now without permafrost.